STRATEGI DAKWAH DIGITAL HANAN ATTAKI DI YOUTUBE - Cikka, Hairuddin; Nurafifah, Nurafifah; Munif, Muhammad; Suharto, Suharto; Najmuddin, Mumhammad (Al-Mishbah: Jurnal Ilmu Dakwah dan Komunikasi, 2024)
The da'wah strategy used by Hanan Attaki is to approach young people, raising the dominant da'wah content that discusses a lot about the discourse of love, the ease and beauty of marriage, life tests, taaruf and so on. In carrying out his da'wah, he often wears a casual appearance typical of young people, such as plaid shirts, collared shirts, t-shirts covered with batik shirts or jackets. One of the typical styles of Hanan Attaki is his appearance which tends to wear a beanie or kupluk hat, beard, thin mustache and box-rimmed glasses. Hanan Attaki as a preacher who is able to carry out studies with interesting themes in accordance with the problems and what young people need. There are several types of content on Hanan Attaki's youtube channel, including themes about disappointment, patience, love, motivation and many more. The influence of Hanan Attaki's da'wah among young people is that many young people want to migrate by studying through Hanan Attaki's youtube account. Abstrak Strategi dakwah yang digunakan Hanan Attaki adalah dengan melakukan pendekatan terhadap anak muda, mengangkat konten dakwah yang dominan banyak membahas menganai wacana cinta, kemudahan dan keindahan menikah, ujian-ujian hidup, taaruf dan sebagainya. Dalam menjalankan dakwahnya, ia kerap berpenampilan kasual khas anak muda, seperti kemeja kotak-kotak, baju berkerah, kaos dilapisi baju batik atau jaket. Salah satu gaya khas dari Hanan Attaki adalah penampilannya yang cenderung meggunakan topi jenis beanie atau kupluk, berjanggut, berkumis tipis dan berkacama berbingkai kotak. Hanan Attaki sebagai pendakwah yang mampu mengusung kajian dengan tema-tema yang menarik sesuai dengan permasalahan dan apa yang dibutuhkan anak muda. Ada beberapa jenis konten di channel youtube Hanan Attaki diantaranya mengenai tema tentang kecewa, sabar, cinta, motivasi dan masih banyak lagi. Adapun pengaruh dakwah Hanan Attaki di kalangan anak muda yaitu, banyak anak muda yang ingin berhijrah dengan belajar melalui akun youtube Hanan Attaki.